Pemodelan Aplikasi Enterprise Resource Planning Untuk Pondok Pesantren (Pemodelan Aplikasi Proses Akademik) - Yaqin, M. Ainul; -, Syahiduzzaman (MATICS, 2016)
Abstract— Pesantren is an institution or organization that is engaged in Islamic religious education-based community education diniyah or integrated with other types of education. As a boarding school organization requires good management information systems by implementing an integrated boarding school. The information system is an Enterprise Resource Planning (ERP) system that covers all business processes in a boarding school and focused on planning and documentation of transactions. ERP is the application used by the manufacturing company in operation. There is therefore a fundamental conceptual differences between the manufacturing process with the process of education at boarding school, so as to generate the appropriate ERP and can be used by the boarding school, the system needs to be modeled. Modelling done by creating a process diagram and diagram data.